Supply Chain Strategy as the Instrument of Marketing on the Example of a Platform in the Global Information Space - Marat Rashitovich Safiullin; Dinara Lenarovna Kurbangalieva; Leonid Alekseevich Elshin (International Journal of Supply Chain Management, 2020)
Abstract— Supply chain strategy of the company is an intangible factor and its evaluation is hard to be filed in physical sense. Meanwhile, in the epoch of digital revolution, when every individual can have duplicate in global information space, we can attempt to evaluate metrics characterizing supply chain strategy on the example of online platforms. Supply chain strategy within information space is studied narrowly, through the prism of marketing researches: exceptionally as the monitoring of feedbacks, searching from the scope of messages negative ones, that is to say feedback management. From another side, among SMM specialists you can find lots of recommendations on websites promotion, laying followers up and so on, but there are so limited researches on key indicator values of results of company supply chain strategy and its reputation on economy influence.  In this article we’ll attempt to evaluate supply chain strategy of company on the basis of open and available information on the example of on-line platform YouTube. On the example of successful company owners (YouTube channels), we’ll find correlation between metrics characterizing supply chain strategy and influence on results of activity - product monetization (video clips) and will define the most valuable ones. Supply chain strategy in this article is shown in new not investigated before format: as the controlling mechanism on platform. Based on research we found that upon the change of metrics characterizing supply chain strategy company revenue varies.